A Comparison between Discrete and Continuous Scanning with Conoscopic Holography. (2015) - Zapico, P.; Fernández, P.; Blanco, D.; Valiño, G.; Rico, J.C.
Abstract: Low density digitizing is a suitable approach for verification distances between pairs of machined flat surfaces. When defining a digitizing procedure of this type of features, two approaches could be applied: discrete or continuous scanning. Discrete Scanning (D) is performed with a static sensor, but the information for each single measurement comes from a constrained area. On the other hand, since Continuous Scanning (C) is carried out with a moving sensor, the information for each single measurement comes from a swept area. In this work, a comparison between these two approaches, when digitizing with a Conoscopic Holography sensor, is performed. The main objective is to establish their influence upon surface reconstruction quality and, thereafter, upon measurement reliability.